Exploring local food purchasing patterns during COVID-19: insights from a nationwide consumer survey - Edmondson, Hailey Elizabeth, author; Thilmany, Dawn, advisor; Jablonski, Becca, committee member; Prasad, Joshua, committee member (Colorado State University. Libraries, 2021)
The onset of the COVID-19 pandemic shocked many aspects of life, and food was no exception. One very large shift that occurred, and was likely influenced by both economic and public health shocks, was in the ways that people purchased food, particularly in the use of new market channels. The following study, as of a larger USDA Agricultural Marketing Service project interested in impacts of COVID-19 on local and regional food systems, investigates local market channel use. In particular, we investigate the extent to which increased interest in local food markets is observed across a national sample and, if so, how it correlates with consumers' behavior-influencing traits like food values and COVID-19 impacts. This study contributes to existing literature through its collection of a large, national consumer survey dataset with a novel focus on local and regional market channels and more in-depth understanding of shifting consumer preferences for non-traditional market channels. We find that a nearly one third of our survey sample used new local and regional market channels during COVID-19, and that individual COVID-19 impacts and values related to local and social welfare were significant predictors of new market channel use. We also find that COVID-19 risk, exposure, and income and employment impacts significantly affect likelihood of new local market adoption. Identifying these traits and values of consumers participating in new market channel behaviors provides valuable insight for local food system practitioners strategizing for a post-COVID future, such as implementing values-based marketing and leveraging technology.
Keywords: direct markets; local market channels; local food; COVID-19